Brazilian guidelines for the management of psychomotor agitation: rapid tranquilization 2 – combinations and special groups - Baldaçara, Leonardo (2021)
In this last article, we compare the different groups of medications, followed by a presentation of possible drug combinations for use in rapid tranquilization. Finally, we address the management of special groups of patients in psychomotor agitation. Systematic review registration: CRD42017054440.